Twin pregnancy and early postpartum pelvic floor surface electromyographic activity: a single-center retrospective observational study using the glazer sEMG protocol - Shushu Yu; Xiaolei Chi; Xiang Ying; Xiaohan Su; Jiawen Yang; Yanlin Wang (Frontiers in Medicine, 2026)
Background Pregnancy and childbirth are established risk factors for postpartum pelvic floor dysfunction. However, the association between twin pregnancy and early postpartum pelvic floor surface electromyographic (sEMG) activity remains unclear. This study explored this association using the Glazer protocol. Methods This retrospective study included 138 primiparous women with twin pregnancies and 540 with singleton pregnancies who underwent cesarean delivery. Pelvic floor sEMG was assessed at 42–60 days postpartum using a modified four-phase Glazer protocol. Between-group differences were examined using univariate analyses and multivariable linear regression. The primary model adjusted for maternal age, pre-pregnancy body mass index, gravidity, and mode of conception. Extended exploratory models additionally included pregnancy- and delivery-related variables and, subsequently, total neonatal birth weight as a potential mediator. Results Compared with the singleton group, the twin group had lower pre- and post-resting mean sEMG amplitudes and higher pre- and post-resting phase scores (all P < 0.05). In the primary adjusted model, twin pregnancy was associated with lower pre-resting (β = −2.029 μV, 95% CI: −3.139 to −0.919; P < 0.001) and post-resting mean sEMG amplitudes (β = −1.310 μV, 95% CI: −2.327 to −0.293; P = 0.012), and higher pre-resting (β = 10.355, 95% CI: 3.967 to 16.742; P = 0.002) and post-resting phase scores (β = 9.011, 95% CI: 2.932 to 15.090; P = 0.004). In the extended model excluding total neonatal birth weight, associations with pre-resting amplitude and pre- and post-resting scores remained significant, whereas the post-resting amplitude association was no longer significant. After adjustment for total neonatal birth weight, none of the associations remained statistically significant. Conclusion In general, the overall Glazer score in the early postpartum period was not significantly lower in women with twin pregnancies than in those with singleton pregnancies. In this exploratory study of primiparous women undergoing prelabor cesarean delivery, twin pregnancy was associated with differences in resting-phase sEMG parameters in the primary adjusted analysis. These associations were attenuated after adjustment for pregnancy-, delivery-, and birth weight–related variables, some of which may lie on the causal pathway. Prospective studies incorporating comprehensive pelvic floor assessments and clinically relevant outcomes are needed.